Role Public Mandatory Lecturers (MKWU) Citizenship Education in Improving Nationalism Attitudes Students University of Riau - Supentri, Supentri; Zahirman, Zahirman; Separen, Separen; Supriadi, Supriadi; Yuliantoro, Yuliantoro (Proceedings of the UR International Conference on Educational Sciences, 2018)
This research is motivated by the importance the role of lecturers general compulsory subjects (MKWU) Citizenship Education, because civic education courses aim to improve student nationalism. Lately, the nationalism of students has begun to fade in terms of behavior, speaking, dressing and being more selfish than common interests. The purpose of this study was to determine the extent to which the role of the lecturer in civic education in improving the nationalism of students at the University of Riau.The method used in this research is Quantitative Descriptive, with a formula P=F/N X 100. Population in this study were all Riau University students, while the sample used Quota sampling which was 20 students per faculty, Riau University consisted of 9 faculties, which meant 180 students. Then the data was collected using questionnaires, interviews and observations.Results of the study showed that of the 12 indicators of the role of lecturers in improving nationalism that were asked to students all indicators had contributed to the respondents answers above 40% of each indicator